1998
DOI: 10.1016/s0896-6273(00)80553-x
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Mediates Calcium-Dependent Inactivation of N-Methyl-D-Aspartate Receptors

Abstract: Ca2+ influx through N-methyl-D-aspartate (NMDA) receptors activates signal transduction pathways critical for many forms of synaptic plasticity in the brain. NMDA receptor-mediated Ca2+ influx also downregulates the gating of NMDA channels through a process called Ca2+-dependent inactivation (CDI). Recent studies have demonstrated that the calcium binding protein calmodulin directly interacts with NMDA receptors, suggesting that calmodulin may play a role in CDI. We report here that the mutation of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
239
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(258 citation statements)
references
References 47 publications
18
239
1
Order By: Relevance
“…This effect would be predicted to reduce the number of NMDA receptors in the activated state (Yu and Salter 1998). Alternatively, perhaps by attenuating intracellular calcium levels, nimodipine may have influenced the phosphorylation state of NMDA receptor subunits and reduced the ketamine sensitivity of these receptors (Zhang et al 1998). A third possibility is that nimodipine and ketamine interacted through opposing modulation of the function of intracellular phosphoproteins, such as calmodulin or cAMP response element-binding protein, whose function might be directly or indireclty sensitive to calcium (CREB) (Deisseroth et al 1998;Ghosh et al 1994;Mermelstein et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This effect would be predicted to reduce the number of NMDA receptors in the activated state (Yu and Salter 1998). Alternatively, perhaps by attenuating intracellular calcium levels, nimodipine may have influenced the phosphorylation state of NMDA receptor subunits and reduced the ketamine sensitivity of these receptors (Zhang et al 1998). A third possibility is that nimodipine and ketamine interacted through opposing modulation of the function of intracellular phosphoproteins, such as calmodulin or cAMP response element-binding protein, whose function might be directly or indireclty sensitive to calcium (CREB) (Deisseroth et al 1998;Ghosh et al 1994;Mermelstein et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that the C-terminal domain has different configurations, which depend on its dynamic interactions with the cytoskeleton. In support of this intriguing possibility, it has been shown that the binding of NR1 to ␣-actinin is displaced by calmodulin (Wyszynski et al, 1997), a process that might explain the calcium-dependent inactivation of NMDA receptors (Ehlers et al, 1996;Zhang et al, 1998;Krupp et al, 1999).…”
Section: Subsynaptic Organization Of Glutamate Receptorsmentioning
confidence: 95%
“…This suggests that an allosteric rather than a channelblocking (Zhang et al, 1998) mechanism is involved in inhibition of single NMDA channel activity by calmodulin. For example, characteristic NMDA channel block, such as that observed with magnesium, is recognized by a distinct fingerprint alteration of the single-channel shut-time distribution (Ascher and Nowak, 1988;Antonov and Johnson, 1999).…”
Section: Inhibition Of Nmda Receptor Single-channel Activity By Calmomentioning
confidence: 99%
“…Several calcium-dependent proteins associated with the postsynaptic density alter NMDA receptor activity, including calmodulin (CaM) (Ehlers et al, 1996;Hisatsune et al, 1997, Rafiki et al, 1997Zhang et al, 1998;Krupp et al, 1999), calcineurin (Lieberman and Mody, 1994;Tong and Jahr, 1994;Tong et al, 1995), protein kinase C (PKC) (Chen and Huang, 1992;Wagner and Leonard, 1996;Xiong et al, 1998;Lu et al, 2000;Lan et al, 2001), and ␣-actinin-2 (Wyszynski et al, 1997;Zhang et al, 1998;Krupp et al, 1999). Therefore, it is generally acknowledged that calcium influx, in part through the NMDA channel, can regulate NMDA receptor activity via various pathways.…”
mentioning
confidence: 99%